A Review of Antineoplastic Agents Associated Nephrotoxicity, an Understood Complication - Hashemieh, Mozhgan (Journal of Pediatric Nephrology, 2020)
In the recent decades, the survival of children with cancer has improved dramatically. This improvement is due to use of different chemotherapeutic agents, but the majority of these drugs have kidney toxicities. Deterioration of renal function due to antineoplastic agents is the main limiting factor for administration of these drugs. Chemotherapeutic agents could result in an acute or chronic injury in glomeruli or tubules. Overall childhood cancer survivors have a nine-fold higher risk of developing kidney function impairment when compared with their sibling. In this review, the nephrotoxicity due to some chemotherapeutic drugs such as platinum agents, ifosfamide, methotrexate(MTX), doxorubicin, gemcitabine and imatinib have been discussed. Keywords: Antineoplastic; Cancer; Chemotherapy; Nephrotoxicity.